Bereavement and grief support for students: The response of Irish schools. - Mc Guckin, Conor; Lynam, Aoife (My University, 2013)
Teachers regularly encounter students who have experienced a significant human loss through bereavement. Research has shown that teachers are increasingly aware of the impact that bereavement and loss has on students? academic performance and their overall social and emotional wellbeing. There is, however, a paucity of empirically-based research exploring such issues within an Irish context. The research outlined in this paper documents the approach and response of primary and post-primary schools regarding policy and provision of support to students who have experienced bereavement. The Bereavement Audit Survey was administered to a representative sample of primary and post-primary schools (N = 1,474). From the first 200 questionnaires returned, preliminary analyses demonstrate that schools are positive, supportive, and proactive whilst also indicating the desire for further support in terms of policy, curricula materials, practice direction, staff support, and Continual Professional Development programmes.
PUBLISHED
.
Keywords: Education; Inclusive Society